An examination of consumer protection and its link to trademark law in Nigeria (2019)
Trademark has an impact on the economic development of any civilised country. A trademark has grave economic value and it is the consumers that suffer harm if the goods and services rendered by the producers are of bad quality. Hence, the aim of a trademark is so that consumers will be able to identify and distinguish between all other goods that are offered up for sale. A trademark could therefore be likened to an indicator of source which serves as a subtle information to consumers that the goods they are about to buy are of good quality. A trademark therefore has economic value that could impact the society either negatively or positively. Hence it is important that the law on trademark should be adequate enough so that the right of consumers would be protected at all times. Apart from that, the law of trademark should not only protect the owners of goods but it should also take the interest of consumers into consideration. As it is now, there is no provision under the Nigerian Trademarks Act of 1965 that specifically provides for consumers that may suffer damage to their health as a result of adulterated goods. The aim of this article is to therefore discuss the link between consumer protection and trademarks. This article will also review the Federal Competition and Consumer Protection Act (FCCPA) to know whether it addresses the interests of consumers. There will also be a brief overview of the other types of trademark and its recognition or not under the Nigerian Trade Marks Act (NTMA) and whether it can be accommodated under the new Consumer Protection Act